2020
DOI: 10.1155/2020/4079098
|View full text |Cite
|
Sign up to set email alerts
|

Pontine Myelinolysis Caused by Hypovolemic Hypernatremia

Abstract: Introduction. Central pontine myelinolysis is characterized by the occurrence of acute demyelinating lesions of cells in the pons secondary to abrupt oscillations of serum osmolarity. Its exact incidence is not well defined, but studies show a prevalence of 0.25 to 0.5% in the general population, 2.5% in the intensive care unit, and up to 10% in patients with risk factors, such as chronic liver disease and hepatic transplantation, alcoholism, malnutrition, diuretic therapy, electrolyte imbalance, hypoglycemia,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
2
0
1
Order By: Relevance
“…55 Furthermore, in a series of retrospectives of medical records about ODS cases, including those between 1960 and 2018 in the US National Library of Medicine, 45,49,[55][56][57][58][59][60][61][62][63] at the Massachusetts General and Brigham and Women's Hospitals and, "using International Classification of Diseases-9th edition codes and a text-based search for central pontine myelinolysis, extrapontine myelinolysis, and osmotic demyelination syndrome (1999-2018)," 56,63 ODS can be more frequently found in intensive care units where about 2.5% emergency care ODS patients can die from it, especially in neonatal and pediatric units. 54,[62][63][64][65][66]67 The same proportion can be reported about the confined aged population [where hyponatremia could cause other motility-related disabilities such health incidents could be preventable, because deficits of homeostatic sodium gradient can cause patient's confusion, disorientation, paresis -including fractures susceptibility [68][69][70][71][72][73][74] deafness, memory loss to seizure, unresponsiveness and eventually coma, [47][48][49][50][51] Thus, in all, the percentage of patients with ODS-associated traumas is also probably more common than reported because, during the recent years, their incidence has augmented due to a more frequent usage of magnetic resonance imaging (MRI) for diagnostic. [73][74][75][76]…”
Section: Discussionmentioning
confidence: 78%
“…55 Furthermore, in a series of retrospectives of medical records about ODS cases, including those between 1960 and 2018 in the US National Library of Medicine, 45,49,[55][56][57][58][59][60][61][62][63] at the Massachusetts General and Brigham and Women's Hospitals and, "using International Classification of Diseases-9th edition codes and a text-based search for central pontine myelinolysis, extrapontine myelinolysis, and osmotic demyelination syndrome (1999-2018)," 56,63 ODS can be more frequently found in intensive care units where about 2.5% emergency care ODS patients can die from it, especially in neonatal and pediatric units. 54,[62][63][64][65][66]67 The same proportion can be reported about the confined aged population [where hyponatremia could cause other motility-related disabilities such health incidents could be preventable, because deficits of homeostatic sodium gradient can cause patient's confusion, disorientation, paresis -including fractures susceptibility [68][69][70][71][72][73][74] deafness, memory loss to seizure, unresponsiveness and eventually coma, [47][48][49][50][51] Thus, in all, the percentage of patients with ODS-associated traumas is also probably more common than reported because, during the recent years, their incidence has augmented due to a more frequent usage of magnetic resonance imaging (MRI) for diagnostic. [73][74][75][76]…”
Section: Discussionmentioning
confidence: 78%
“…This murine investigation model would suggest that a longer time lapse into ODS repairs could be investigated to understand the clinical resolution of such regional CNS neuropathology [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]219 because similar human ODS clinical cases remained with some concerns even if for most patients the prognosis is generally favorable. 7,[220][221][222] However, a recent retrospective analysis indicated that, post hospitalization, 1 out of 6 ODS patients had died 6 months later, due to other underlying disease states.…”
Section: Clinical Considerationsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] The ODS neuropathologic syndrome is caused by a hastily adjustment of a temporary or chronic deficiency of the homeostatic sodium gradient as it can be pertinent to diverse homeostatic hormonal sodic perturbations such as those afflicted by exaggerated body fluid losses and emergently treated for alcoholism, diabetes as well as to defective dialysis. [1][2][3][9][10][11][12][13][14] A large reference list of ODS literature was recently cited [15][16][17][18][19] and it appeared that EPM lesions can appear before any CPM ones [19][20][21][22][23][24][25] and ODS in human EPM cases would be more frequent than CPM ones. 23 There, ODS can frequently appear clinically in the elderly, hospitalized population.…”
Section: Introductionmentioning
confidence: 99%
“…Beraldo и соавт. [10] опубликовали описание случая ЦПМ, развившегося у больного при длительном лечении диуретиками с гипофосфатемией, гипокалиемией и гипомагниемией.…”
unclassified